2022
DOI: 10.1186/s12913-022-07785-x
|View full text |Cite
|
Sign up to set email alerts
|

A framework to support the progressive implementation of integrated team-based care for the management of COPD: a collective case study

Abstract: Background In Canada, there is widespread agreement about the need for integrated models of team-based care. However, there is less agreement on how to support the scale-up and spread of successful models, and there is limited empirical evidence to support this process in chronic disease management. We studied the supporting and mitigating factors required to successfully implement and scale-up an integrated model of team-based care in primary care. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“… 35 In a region of Canada, an IDM known as Best Care COPD has been shown to improve patient outcomes. 36 , 37 In Switzerland it been suggested that advanced practice nurses may also be able to play a key role within a multi-professional team in future models of care to coordinate patient care across sectors. 38 Increased use of telehealth technologies for pulmonary rehabilitation or remote consultations, likely to have been accelerated by the COVID-19 pandemic, are also providing additional options for care models.…”
Section: Discussionmentioning
confidence: 99%
“… 35 In a region of Canada, an IDM known as Best Care COPD has been shown to improve patient outcomes. 36 , 37 In Switzerland it been suggested that advanced practice nurses may also be able to play a key role within a multi-professional team in future models of care to coordinate patient care across sectors. 38 Increased use of telehealth technologies for pulmonary rehabilitation or remote consultations, likely to have been accelerated by the COVID-19 pandemic, are also providing additional options for care models.…”
Section: Discussionmentioning
confidence: 99%
“…17 Further evaluative studies of the Best Care COPD Programme supported real-world effectiveness, reporting that Best Care improved patient and provider experiences, and that it was cost-effective and dominant relative to the usual standard of care. [18][19][20][21][22][23] As with the majority of studies forming a large body of published literature on IDM, the quantitative evaluations were limited to 1 year of locally collected follow-up data. 13 Additionally, even for pulmonary rehabilitation, a gold-standard COPD IDM intervention, the long-term impacts are unproven.…”
Section: What This Study Addsmentioning
confidence: 99%
“…A critical element of this selection process was consensus and evidence that local assets (notably the Best Care Team) could be leveraged within this sub-population to generate improvement in experiences, outcomes, and total cost of care across the system. 19 , 20 WOHT leveraged ongoing and established work to support this population as a way to make an even greater impact on the equity-driven Quadruple Aim, specifically health outcomes and patient and provider experiences. It was also felt that this sub-population offered a foundation for change that could demonstrate the principles of integrated care and population health management extending beyond traditional medical care.…”
Section: Early Days (Committing To a Vision)mentioning
confidence: 99%